Development of antioxidant-rich purple sweet potato (Ipomoea batatas L.)-based extruded breakfast cereal - Senevirathna, Sri Sampath Janaka (2022)
Ready-to-eat extruded breakfast cereal is extremely popular among consumers because it is easy and very convenient to prepare, but is often loaded with sugars and unhealthy food additives. The increasing demand of consumers toward functional foods triggers the development of ready to eat breakfast cereals rich in antioxidant. Purple sweet potato powder (PSPP) which is rich in anthocyanins and other polyphenols, provides excellent antioxidant and other biological activities with potential health benefits to the consumers. Therefore, the main objective of this study was to develop an antioxidant-rich extruded puffed breakfast cereal from PSPP as the main ingredient. The anthocyanin content and colour of purple sweet potato are influenced by drying methods and processing conditions. In the first part of this study, the effects of citric acid (CA) concentration, steam pressure (SP) and drum rotation speed (DS) on the physicochemical and functional properties of drum-dried PSPP were investigated by response surface methodology (RSM). The results indicated that the moisture content (MC) and water activity (aw) significantly (p<0.05) decreased with increasing SP and reduced DS. Addition of CA significantly (p<0.05) affected the colour and total anthocyanin content (TAC) of PSPP. High SP and low DS negatively influenced the antioxidant properties of PSPP, with the optimal physicochemical and functional properties of drum dried PSPP achieved at 0.59% CA, 499.8 kPa SP and 3.0 rpm DS. Twelve anthocyanins were identified by HPLC-MS/MS; and it was observed that cyanidine based anthocyanins were dominant in PSPP. The second part of the research evaluated the effect of formulation on the physiochemical, textural and functional properties of the PSP-based extruded puffed breakfast cereals prepared from a mixture of PSPP (30.0%-70.0%), wholegrain red rice flour (WRRF) (15.0%-50.0%) and (cornflour) CF (15.0%-50.0%) using a single screw extruder via a D-optimal mixture design approach. The findings demonstrated that PSPP, WRRF and CF had a pronounced effect on the extrudates' textural and functional properties. The PSPP indicated a most significant positive impact on antioxidant capacity, whereas the CF contributed towards a better expansion of the final product. The optimum formulation of breakfast cereal with an acceptable textural properties and highest antioxidant properties was produced using 55.0% PSPP, 15.0% WRRF and 30.0% CF. In the third part of this research, the RSM was used to optimise the extrusion processing condition for the development of breakfast cereals. The independent variables studied include barrel temperature, screw speed and feed moisture in the range of 140.0°C-180.0°C, 100.0 rpm - 140.0 rpm and 13.0%-18.0%, respectively. All the responses were significantly affected by the process variables. The linear terms of barrel temperature and feed moisture content were found to be the main significant (p<0.05) factors affecting the product's functional and physicochemical properties. The expansion property of extrudate was significantly (p<0.001) increased at low temperature, high screw speed and low feed moisture. The recommended optimum extrusion conditions of barrel temperature, screw speed and feed moisture content were at 157.0°C, 126.0 rpm and 13.0%, respectively. Under these optimum conditions, significantly high retention (75.0%) of anthocyanin content was detected in the final extruded product. Furthermore, the scanning electron micrographs depicted that the optimised breakfast cereals had a better cell structure with smoother and thin cell walls than the non-optimised samples. The final part of this study investigated the effect of packaging on the physicochemical and functional properties of antioxidant-rich PSP-based breakfast cereal under accelerated conditions (38.0±1.0°C, 90.0% relative humidity) packaged in metalised (MET) and polypropylene (PP) pouches for 12 weeks. The magnitude of quality changes of packaged PSP breakfast cereals was monitored throughout the storage period. The colour change, TAC reduction, MC and aw gain of breakfast cereals followed zero order kinetics during storage, and the half-life of anthocyanin was recorded as 24.63 and 10.13 weeks for MET and PP, respectively. The kinetic constant for all properties studied was higher for the product packed in PP than MET pouches. It was observed that moisture migration is the limiting factor of the shelf-life of the PSP breakfast cereals. Sensory analysis results showed that the PSP extruded product had an average overall acceptability score ranging from 7.15 to 8.29 indicating the panellists like the product moderately to very much. In conclusion, an extruded puffed breakfast cereals with attractive natural purplish-red colour and acceptable functional properties was successfully developed in this study.